NetMenu and a Prototype UMLS Information Sources Map - Miller, Perry L. (1993)
The demonstration will show NetMenu and an Information Sources Map (ISM), two tools being developed to help the biomedical user find out about a range of network-based information sources, and to connect automatically to a chosen source. Both NetMenu and the ISM are operational at Yale, and available for use elsewhere.